Characterization of the sensitization profile to lupin in peanut‐allergic children and assessment of cross‐reactivity risk. Issue 3 (3rd April 2013) - Ballabio, Cinzia; Peñas, Elena; Uberti, Francesca; Fiocchi, Alessandro; Duranti, Marcello; Magni, Chiara; Restani, Patrizia
Abstract Background Case reports of allergy to lupin, due to primary sensitization or cross‐reactions with other legumes, are increasing as a consequence of the augmented use of lupin flour in bakery, pasta formulations and other food items. The main allergens that have been associated with the sensitization to lupin are α‐ and β‐conglutins and, to a lesser extent, γ‐ and δ‐conglutin, but no conclusive data are available so far. The aim of this study was to characterize the sensitization pattern to lupin in a group of 12 Italian children allergic to peanut and identify the specific lupin proteins involved in the cross‐reactivity with peanut. Methods The immunochemical cross‐reactivity among peanut and lupin was evaluated by both in vitro immunoblotting and in vivo fresh food skin prick test (FFSPT). Results The results showed that β‐conglutin was recognized by cutaneous IgEs from 7/12 peanut‐allergic children in FFSPT and serum IgEs from 5/12 in immunoblotting, while 4/12 and 8/12 patients tested positive to γ‐conglutin in FFSPT and immunoblotting, respectively. No significant immunoreactive responses were observed to α‐ and δ‐conglutins under non‐reducing conditions, but they were bound in FFSPT by the sera of 5/12 and 3/12 patients, respectively. Conclusion In this group of allergic children, β‐conglutin has been identified as the major lupin allergen involved both in vitro and in vivo cross‐reactivity with peanut proteins. The role of γ‐conglutin in the cross‐reactivity between lupin and peanut proteins was also relevant and clear, despite the observed unspecificity of the immunoblotting responses.